2020
DOI: 10.21203/rs.3.rs-76318/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T cell anergy in COVID-19 reflects virus persistence and poor outcomes

Abstract: Coronavirus disease 2019 (COVID-19) can lead to severe pneumonia and hyperinflammation. So far, insufficient or excessive T cell responses were described in patients. We applied novel approaches to analyze T cell reactivity and showed that T anergy is already present in non-ventilated COVID-19 patients, very pronounced in ventilated patients, strongly associated with virus persistence and reversible with clinical recovery. T cell activation was measured by downstream effects on responder cells like basophils, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…T-cell anergy is also considered as a hallmark of SARS-CoV-2induced disease and is correlated with severity of the condition (95). Results of a study showed more pronounced hyporeactive T cells in hospitalized patients with a SARS-CoV-2-induced disease, and such severe hyporeactive T cells are correlated with prolonged viral persistence.…”
Section: Hyper/hypo Active and Senescent T Cellsmentioning
confidence: 99%
“…T-cell anergy is also considered as a hallmark of SARS-CoV-2induced disease and is correlated with severity of the condition (95). Results of a study showed more pronounced hyporeactive T cells in hospitalized patients with a SARS-CoV-2-induced disease, and such severe hyporeactive T cells are correlated with prolonged viral persistence.…”
Section: Hyper/hypo Active and Senescent T Cellsmentioning
confidence: 99%